Socio-Economic Effects of Mega Sports Events - DÜZEN, Arif Çağatay; KARGÜN, Mehmet; ÇELİK, Talip (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2022)
It is seen that the effects of sports on the person both biologically and psychologically are undeniable. In addition to the benefits that sports provide to individuals, sports have become an important tool in terms of supporting local and regional development with effects such as creating marketing opportunities to countries, promoting them and increasing the value of brands. This study aims to examine the effects of mega sports events on cities and countries. In the study, the document analysis model, one of the qualitative research methods, is adopted. In this context, the resources related to the subject will be scanned as archives and brought together and examined. In document analysis, the data is systematically collected, analyzed and evaluated. In this context, previous scientific studies on the subject, statistical information and mathematical data have been taken into consideration. Considering the findings of the research, the cost and profit table of the Olympic Games held between 1996 and 2016 has been explained. In Table 2, the income statement of the International Federations in some Summer and Winter Olympic Games is given. In Table 3, the income of the Olympic Committee according to some years and in Table 4, information about the income status of the FIFA World Cups held in 1978 and 2018 are given. When we look at the data obtained, mega sports events have rapidly increased the number of viewers. As a result, sports tourism has developed in cities where mega sports events are held. At the same time, cities have felt many socio-economic impacts. The newly built sports halls for mega sports events have both created positive effects on cities and have an important place in the field of employment. Besides, sports sponsorships and side stakeholders related to sports were significantly affected by mega sports events. Consequently, mega sports events have many important effects in many different ways on the cities where they are organized. Especially in the long term, it can have positive effects that support the promotion of the country, the development of athletes, and the establishment of sports. These can be listed as sports sponsorship, employment, establishment and side stakeholders of sports.